The implementation of partial graph heuristic with improvement method to solve the UMP examination timetabling problem - Lee Jian, Hao (2013)
The examination timetabling problem has attracted the interested of many researchers over the years. However, this problem is difficult to solve due to the lack of benchmark dataset and many constraints that need to be satisfied in examination timetabling problem. Currently, Universiti Malaysia Pahang (UMP) use proprietary system to generate the examination timetable but the weakness of this system is unable to define the quality of solution because having no evaluation function. Other than that, the UMP examination timetabling problem consist unique constraints such as distance penalty and split penalty. Having all of these constraints had made the task to solve examination timetabling problem becomes more challenging. To produce examination timetable, all of the exams need to be scheduled into timetable while satisfying the hard constraint and soft constraint. The timetable result should have the minimum penalty value in terms of spread exams, split rooms and distance between rooms. Therefore, the technique partial graph heuristic with hill climbing method should be implemented to solve UMP examination timetabling problem. The graph heuristic method will partially schedule the exam and then improved by hill climbing method. This process will be continued until finish scheduled all of the exams. By using this technique, the solution of timetable result can comply all of the constraint and has a better quality of solution compared to the result of current examination system.